Emotions and investments: the influence of investor sentiment on cryptocurrencies during the Covid-19 pandemic - Rayane Farias dos Santos; César Augusto Tibúrcio Silva (Revista Ambiente Contábil)
Purpose: The study analyzed the relationship between investor sentiment and the return and trading volume of the main cryptocurrencies in Brazil during the COVID-19 pandemic.